2006
DOI: 10.1592/phco.26.11.1616
|View full text |Cite
|
Sign up to set email alerts
|

Management of Antiplatelet Therapy for Minimization of Bleeding Risk Before Cardiac Surgery

Abstract: Antiplatelet therapy is commonly administered for primary and secondary prevention of stroke, recurrent angina, myocardial infarction, and death in patients with cardiovascular disorders. It also is associated with an increased risk of bleeding. We describe the management of antiplatelet therapy in patients undergoing coronary artery bypass graft surgery. In addition, we provide basic information about the mechanisms of action by which the most common antiplatelet agents inhibit platelet function. This informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…4 Avoidance of unnecessary blood transfusion and reduction of transfusion requirements are of great importance to minimize these transfusion-related adverse events. 23 Shore-Lesserson et al 8 and Weant et al 24 reviewed the evidence supporting the use of POC monitors in coagulation and hemostasis management in cardiac surgery. The authors concluded that the ability to accurately measure platelet function has shown great benefits in the perioperative setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Avoidance of unnecessary blood transfusion and reduction of transfusion requirements are of great importance to minimize these transfusion-related adverse events. 23 Shore-Lesserson et al 8 and Weant et al 24 reviewed the evidence supporting the use of POC monitors in coagulation and hemostasis management in cardiac surgery. The authors concluded that the ability to accurately measure platelet function has shown great benefits in the perioperative setting.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of the platelet function defect of CPB (drugs, fibrinolysis, receptor defect, contact activation, hypothermia) partly explains the difficulty investigators have had in consistently measuring it. 8,24 Weber et al's analysis is the first and the only prospective, randomized clinical trial in cardiac surgery that investigated the efficacy of POC testing including platelet function testing versus conventional coagulation analyses. The author revealed a significant difference in erythrocyte transfusion rate in the conventional compared with the POC group (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment duration has recently been considerably extended from a few months to over a year after drug-eluting stent insertion in order to avoid late thrombosis (5). However, widespread combined antiplatelet agents (cAPA) therapy increases the risk of spontaneous bleeding (6,7), and haemorrhage in case of head trauma (8) or elective surgery (9,10). Although most surgical procedures can usually be carried out safely without interrupting antiplatelet therapy, some procedures (mainly neurosurgery and prostate surgery) still require preoperative withdrawal, which potentiates the risk of thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…19,27,29 P reoperative use of such agents has been associated with postoperative bleeding complications, especially when used in combination. [28][29][30] Severe cardiac insuffi ciency often leads to congestion-related hepatic dysfunction, which can cause defi ciencies of the coagulation factors and predispose patients to severe bleeding if untreated. In some VAD implant centers, patients are treated preoperatively with vitamin K to correct international normalized ratio.…”
Section: Right Ventricular Dysfunctionmentioning
confidence: 99%